Answer:
B.6
Step-by-step explanation:
When we add and subtract, we do it from left to right
13+ (-12) - (-5)
13+-12
13-12 = 1
1 - -5
A negative negative is a positive
1 +5
6
Answer: <em>"7 is a solution to the original equation. The value –1 is an extraneous solution."</em>
Step-by-step explanation:
The equation can be solved by squaring both sides:
We can see that -1 and 7 are solutions, but make sure they are not extraneous by substituting them in the original equation:
The square root of 49 equals 7, but the square root of -1 is an imaginary number.
The correct choice is <em>"7 is a solution to the original equation. The value –1 is an extraneous solution."</em>
X + 5 + 11x = 12x + y
Simplify: 12x + 5 = 12x + y (We are adding x and 11x on the left side)
Subtract 12x from each side makes each zero.
5 = y
So we can plug in and test. I'm picking two random numbers to plug in for x. 10, and 82
x = 10, y = 5
10 + 5 + 11(10) = 12(10) + 5
125 = 125
x = 82, y = 5
82 + 5 + 11(82) = 12(82) + 5
989 = 989
So we verified y = 5
Answer:
<u>Secant</u>: a straight line that intersects a circle at two points.
<u>Intersecting Secants Theorem</u>
If two secant segments are drawn to the circle from one exterior point, the product of the measures of one secant segment and its external part is equal to the product of the measures of the other secant segment and its external part.
From inspection of the given diagram:
- M = Exterior point
- MK = secant segment and ML is its external part
- MS = secant segment and MN is its external part
Therefore:
⇒ ML · MK = MN · MS
Given:
- MK = (x + 15) + 6 = x + 21
- ML = 6
- MS = 7 + 11 = 18
- MN = 7
Substituting the given values into the formula and solving for x:
⇒ ML · MK = MN · MS
⇒ 6(x + 21) = 7 · 18
⇒ 6x + 126 = 126
⇒ 6x = 0
⇒ x = 0
Substituting the found value of x into the expression for KL:
⇒ KL = x + 15
⇒ KL = 0 + 15
⇒ KL = 15
Answer:
x = 6.6
Step-by-step explanation:
Data obtained from the question include the following:
Angle X = 15°
Angle Y° = 23°
Side y = 10
Side x =..?
The value of side x can be obtained by using the sine rule as shown below:
x/Sine X = y/Sine Y
x/Sine 15 = 10/Sine 23
Cross multiply
x × Sine 23 = 10 × Sine 15
Divide both side by Sine 23
x = (10 × Sine 15) / Sine 23
x = 6.6
Therefore, the value of x is 6.6.